PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING MENGGUNAKAN MEDIA PhET TERHADAP KETERAMPILAN PROSES SAINS SISWA - Parno Mahulae (Charm Sains: Jurnal Pendidikan Fisika, 2023)
The purpose of this study was to: analyze whether the results of students' science process skills using the inquiry training learning model were better than conventional learning. This research was a quasi-experimental study with a two-group pretest-posttest design. The research population was all class X students of SMA Negeri 19 Medan in the even semester of the 2021/2022 academic year. Sampling was determined by random cluster sampling with two classes consisting of 66 students. Class X-2 as an experimental class with a scientific inquiry learning model totaling 33 students, class X-1 as a control class with conventional learning totaling 33 students. The research instrument used a science process skills description test that was valid and reliable. The results of data analysis using two-way Anava. The results showed that the science process skills of students using the inquiry training learning model were better than conventional learning.